SDFMUCR: Software-defined and fuzzy-based multi-hop unequal cluster routing - Lu Sixu; Wu Muqing; Zhao Min (International Journal of Distributed Sensor Networks)
Recently, wireless sensor networks play an important role in our life. Researchers give more and more attention to the design of the routing algorithm. Cluster routing is the most popular routing protocol in wireless sensor networks. However, hotspot problem always exists. Unequal cluster routing is an effective method to solve this problem. In these protocols, nodes closer to base station have the smaller cluster size than other sensor nodes. It will reduce the relay pressure of the node which is near to the base station. The development of the software-defined network optimizes the performance of wireless sensor networks. In this article, we propose a software-defined and fuzzy-based multi-hop unequal cluster routing protocol. It adopts three methods to make the routing protocol outstanding. First, it uses a novel software-defined network architecture to reduce computation overhead and energy overhead in sensor nodes. Then, the fuzzy logic–based intracluster and intercluster routing is designed to balance energy consumption. Finally, residual energy–based rotating scheme is proposed to reduce most of the control overhead. According to the simulation results, the proposed protocol balances and reduces the energy consumption, extends the lifetime, and reduces the control overhead and latency of the network.